Patient factors related to early implant failures in the edentulous jaw: A large retrospective case–control study. (17th May 2021) - Malm, Malin Olsson; Jemt, Torsten; Stenport, Victoria Franke
Abstract: Background: Dental implants provide anchorage for dental prostheses to restore functions for individuals with edentulous jaws. During the healing phase, proper osseointegration is required to prevent early implant failure. More knowledge is needed regarding factors related to early failure of dental implants. Purpose: The aim of the present study was to identify possible risk factors for early implant failure, with respect to anamnestic and clinical parameters. Materials and Methods: All patients with edentulous jaws with early implant failure (n = 408) from one referral clinic were compared with a matched control group (n = 408) with no implant failure. Early implant failure was identified during the first year of prosthetic function. Matching was performed on age, gender, year of surgery, type of jaw, and type of implant surface. In addition, data on anamnestic and clinical parameters were collected. The data were analyzed with a multivariable logistic regression model using early implant failure as the binary outcome. Results: Five anamnestic factors were statistically significant with respect to higher probability for early implant failure: systemic disease, allergies in general, food allergies, smoking, and intake of analgesic medication. Four clinical conditions (i.e., implants in the opposing jaw, low primary stability, reduced bone volume, and healing complications) were also related to higher probability for early implant failure. Conclusions: This study identified nine factors associated with early implant failure, several related to patient's general health. Further investigations are needed to fully understand the causality between the obtained variables and early implant failure.